1983
DOI: 10.1079/bjn19830049
|View full text |Cite
|
Sign up to set email alerts
|

Studies on gastric digestion of protein and carbohydrate, gastric secretion and exocrine pancreatic secretion in the growing pig

Abstract: 1. We have investigated the relations between changes in plasma insulin and 3,5,3'-triiodothyronine (T,), and muscle growth and protein turnover in the rat in response to diets of varying protein concentrations.2. Young rats were fed ad lib. on a control (180 g casein/kg) diet or low-protein diets containing 80, 45 and 0 g casein/kg in four separate experiments. Measurements were made of food intakes, muscle and body-weight growth rates, muscle protein turnover in vivo, plasma insulin, and plasma free and tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
1
2

Year Published

1987
1987
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(66 citation statements)
references
References 31 publications
(24 reference statements)
2
61
1
2
Order By: Relevance
“…Protein turnover in rats varies markedly in response to the adequacy of protein intake (Waterlow et al 1978;Jepson et al 1988). However, careful studies in human subjects indicate that protein turnover is in fact insensitive to protein or amino acid intake over a wide range (Marchini et al 1993;Zello et al 1993).…”
Section: Indicators Of Adequacymentioning
confidence: 99%
“…Protein turnover in rats varies markedly in response to the adequacy of protein intake (Waterlow et al 1978;Jepson et al 1988). However, careful studies in human subjects indicate that protein turnover is in fact insensitive to protein or amino acid intake over a wide range (Marchini et al 1993;Zello et al 1993).…”
Section: Indicators Of Adequacymentioning
confidence: 99%
“…9 the anabolic drive can be conceived in terms of exerting homeostatic and homeorhetic influences as well as exerting some functional regulation. Dietary protein is well known to regulate the growth of skeletal muscle (Jepson et al 1988) and in children growth in height may be another indicator of homeorhetic control by protein, at least according to the evidence assembled by Golden (1985).…”
Section: J M I L L W a R D And Othersmentioning
confidence: 99%
“…Several studies indicated that RNA activity represented the changes in the translational phase of tissue protein synthesis (26). Little information on the mechanism by which dietary ornithine or arginine regulates RNA activity in the brain of young rats is available.…”
Section: Resultsmentioning
confidence: 99%